Physicochemical and microbiological evaluation of water for human consumption in six rural High Andean communities of Huancavelica-Peru - GONZALES SAENZ, WOHLER (2023)
In the high Andean rural area of ​​Perú, it is important to monitor the quality of water according to the goals and indicators of sustainable development corresponding to its availability, its accessibility, and that these are free of fecal and chemical contamination. In this regard, there is limited information on the quality of water for human consumption that does not support those involved in the correct management of water with efficient intervention strategies. Therefore, the objective of this research was to contribute with updated information on the status of water quality in six high Andean rural communities in the department of Huancavelica in Peru, corresponding to physicochemical and microbiological parameters. The communities were Antaccocha, Huaylacucho, Pampachacra, Pueblo Libre, San Gerónimo and Sachapite located between 3782 m.a.s.l. and 4196 m.a.s.l. that house a total of 17 water reservoirs where the study was carried out. The physicochemical evaluation included variables such as turbidity, electrical conductivity, pH, total dissolved solids and oxidation potential; the microbiological included the evaluation of Echericha Coli, thermotolerant and fecal coliforms. As a result, only 1/17 (5.9%) sampling point has exceeded the turbidity limit value of 5 NTU allowed by Peruvian regulations; the other parameters are within the allowed threshold. Regarding the microbiological parameters (Echericha Coli, thermotolerant and fecal coliforms), 4/17 (23.5%) monitoring points have exceeded the limit value allowed by the regulation of water for human consumption; Likewise, it has been found that these three parameters are related.